Branched tetrameric lactoferricin peptides modified with diaminopropionic acid exhibit potent antimicrobial and wound-healing activities - Vavilthota, Nikitha; Babuççu, Gizem; Cordfunke, Robert A.; de Boer, Leonie; Balraadjsing, Payal; Boekema, Bouke K. H. L.; Drijfhout, Jan W.; Riool, Martijn; Zaat, Sebastian A. J. (Frontiers in Pharmacology, 2025)
IntroductionInfected chronic wounds present a dual therapeutic challenge, requiring both the eradication of pathogens and the restoration of tissue homeostasis. Often the current treatments are ineffective against multidrug-resistant (MDR) pathogens and fail to promote wound healing. Antimicrobial peptides, such as bovine lactoferricin (LfcinB), offer a promising alternative owing to their broad-spectrum activity and immunomodulatory properties. The branched tetrameric LfcinB-derived peptide (LBT; (RRWQWR)4K2Ahx2-C2) is particularly attractive, as its multivalent architecture enhances antimicrobial potency and provides a tunable branching core for structural modifications.MethodsIn this study, three novel tetrameric variants were designed by substituting the L-lysine branching residues in LBT with non-natural lysine derivatives to alter motif orientation and linker flexibility. Among the novel peptides, the diaminopropionic acid (DAP)-modified variant, (LBT-1; (RRWQWR)4DAP2Ahx2-C2) was selected as best-performing candidate based on antimicrobial and hemolytic activity assessment.ResultsCompared to LBT, the novel LBT-1 demonstrated superior activity against methicillin-resistant Staphylococcus aureus (MRSA) and MDR Acinetobacter baumannii, achieving rapid bactericidal action within 5 minutes. LBT-1 also exhibited potent activity across the ESKAPE(E) panel and against the emerging MDR fungal pathogen Candidozyma auris. Beyond direct antimicrobial effects, LBT-1 enhanced macrophage-mediated bacterial clearance, neutralized endotoxins, and accelerated wound closure in vitro. Importantly, LBT-1 showed superior pro-angiogenic activity in vitro and achieved significantly higher bactericidal activity against MRSA in an ex vivo human skin wound infection model. This study identifies LBT-1 as a multifunctional therapeutic that addresses key pathological features of chronic wounds.ConclusionTogether, these findings validate our peptide design strategy, revealing previously unknown characteristics of the LBT peptide and the enhanced multifunctionality achieved with LBT-1, supporting its continued development for chronic wound management.